People's Republic of China Financial Sector Assessment Program : Systemic Oversight of Financial Market Infrastructures - International Monetary Fund; World Bank Group (World Bank, Washington, DC, 2018)
China's landscape for Financial Market Infrastructures (FMIs) is one of the largest and most complex in the world. It consists of a range of payment, clearing and settlement systems, including several interbank payment systems, securities settlement systems and central counterparties (CCPs). Many of the systems have high volumes by international comparison and are systemically important at a national level. Disruptions, both operational and financial, in one of these FMIs may significantly impact the functioning of the Chinese economy. The landscape is subject to changes, following international developments, such as the establishment of a cross-border interbank payment system (CIPS) and a CCP for over-the-counter derivatives. The development of new, innovative products, for example, in the area of internet payments, is changing the landscape further.